2016
DOI: 10.1128/jcm.00318-16
|View full text |Cite
|
Sign up to set email alerts
|

Role of Antifungal Susceptibility Testing in Non-Aspergillus Invasive Mold Infections

Abstract: No clinical breakpoints are available to delineate antifungal drug efficacy in non-Aspergillus invasive mold infections (NAIMIs). In this analysis of 39 NAIMI episodes, the MIC of the first-line antifungal drug was the most important predictor of therapeutic response. For amphotericin B, an MIC of <0.5 g/ml was significantly associated with better 6-week outcomes.M olds other than Aspergillus spp. account for an increasing proportion of invasive fungal infections in the expanding population of immunosuppressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…There seems to be some correlation between the degree of susceptibility of Mucorales isolates to amphotericin B and outcomes. In a small study by Lamoth et al ., an MIC of not more than 0.5 μg/mL was significantly associated with better 6-week outcomes 131 . Liposomal amphotericin B is the drug of choice for first-line treatment.…”
Section: Rare Moldsmentioning
confidence: 88%
“…There seems to be some correlation between the degree of susceptibility of Mucorales isolates to amphotericin B and outcomes. In a small study by Lamoth et al ., an MIC of not more than 0.5 μg/mL was significantly associated with better 6-week outcomes 131 . Liposomal amphotericin B is the drug of choice for first-line treatment.…”
Section: Rare Moldsmentioning
confidence: 88%
“…The fact that NAIMIs are uncommon diseases and that the outcome depends on multiple factors (Table 1) with a key role of nonpharmacologic parameters (e.g., stage of the fungal infection at time of diagnosis, activity of underlying disease, comorbidities, and recovery of immunosuppression) renders this assessment particularly difficult. Indeed, studies attempting to correlate MICs and outcome in opportunistic mold infections, including NAIMIs, in high-risk hematology patients are scarce (9,(12)(13)(14). Differences between in vitro artificial AST conditions and the complexity of in vivo infections are illustrated in Fig.…”
Section: In Vitro Activity Of Antifungalsmentioning
confidence: 99%
“…For amphotericin B, MICs are distributed in a narrower range, with values rarely exceeding 4 g/ml (16). One small retrospective study suggested that amphotericin B MICs of Յ0.5 g/ml were associated with a better response to therapy (9). Most importantly, prompt initiation of amphotericin B therapy is crucial for outcome, with a rate of mortality that was twice higher among patients for which therapy was delayed (Ն6 days from diagnosis) (61).…”
Section: Efficacy Of Antifungals In Vivomentioning
confidence: 99%
“…Clinically, it is difficult to distinguish NAIMIs from invasive aspergillosis (IA), and NAIMIs often have a progressive and aggressive course . NAIMIs should be distinguished from IA primarily because many of these non‐ Aspergillus moulds are not susceptible to or are intrinsically resistant to azoles, including voriconazole . This may lead to treatment failure and increased mortality.…”
Section: Introductionmentioning
confidence: 99%
“…10 NAIMIs should be distinguished from IA primarily because many of these non-Aspergillus moulds are not susceptible to or are intrinsically resistant to azoles, including voriconazole. [13][14][15] This may lead to treatment failure and increased mortality. However, data for the epidemiology of NAIMIs are limited, owing to its rarity and the lack of microbiological confirmation.…”
Section: Introductionmentioning
confidence: 99%